(untitled) (مجلة البحوث الأكاديمية, 2016)
this study was designed to examine the factors influencing the knowledge and attitudes of hospital workers towards recycling of hospital waste. A total of 1500 were sent to the three Libyan hospitals , 500 questionnaires were distributed to the each hospitals, the response rate were (83.33%). Females workers and nurses responded significantly more frequently than men workers and physicians. In general there were relatively low levels of knowledge about waste management and recycling practice. None of the Libyan hospitals practiced any recycling and the hospital workers in Libya were significantly enthusiastic towards recycling. Training in hospital waste management and education were found to be weak predictors of positive attitudes. The results showed that it is difficult to predict the recycling behaviours among hospital workers. However, waste management staff were more positive towards recycling than those without training in waste management